Modeling of an optical diaphragm for human pulse pressure detection - Hasikin, K.; Soin, N.; Ibrahim, F. (2008)
This paper presents the modeling of an optical diaphragm behavior for human pulse pressure detection. In this study, the comparison between the performance of the polyimide and silicon nitride diaphragm has been presented. The effects of diaphragm radius and diaphragm thickness on static and frequency response are also investigated. The findings show that the polyimide diaphragm is more sensitive than the silicon nitride diaphragm. In addition, deflection of both diaphragms has linear relationship with the applied pressure The diaphragm radius has more effect on the deflection, sensitivity and resonance frequency as compared to the diaphragm thickness. It can be concluded that the polyimide diaphragm achieves the optimum performance in terms of the deflection, sensitivity, and resonance frequency for human pulse pressure detection. Thus, the polyimide diaphragm has been chosen as the best model in designing an optical micro-diaphragm.